Elections, Contracts and Markets - Hans Gersbach; Markus Müller (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
As the performance of long-term projects is not observable in the short run politicians may pander to public opinion. To solve this problem, we propose a triple mechanism involving political information markets, reelection threshold contracts, and democratic elections. An information market is used to predict the long-term performance of a policy, while threshold contracts stipulate a price level on the political information market that a politician must reach to have the right to stand for reelection. Reelection thresholds are offered by politicians during campaigns. We show that, on balance, the triple mechanism increases social welfare.
Keywords: D72; D82; 330; elections; threshold contracts; democracy; information markets; triple mechanism; Politiker; Politisches Ziel; Wahl; Wahl; Öffentliche Meinung; Informationsmarkt; Wohlfahrtsanalyse; Spieltheorie